2012
DOI: 10.1371/journal.pone.0041719
|View full text |Cite|
|
Sign up to set email alerts
|

IL-6 Indirectly Modulates the Induction of Glyceroneogenic Enzymes in Adipose Tissue during Exercise

Abstract: BackgroundGlyceroneogenesis is an important step in the control of fatty acid re-esterification with PEPCK and PDK4 being identified as key enzymes in this process. We have previously shown that glyceroneogenic enzymes such as PDK4 are rapidly induced in white adipose tissue during exercise. Recent studies have suggested that IL-6 regulates adipose tissue metabolism and gene expression during exercise. Interestingly, IL-6 has been reported to directly decrease PEPCK expression. The purpose of this investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 38 publications
2
39
1
Order By: Relevance
“…In support of this, in whole body IL-6 knockout mice, the glucose lowering effects of CL were indistinguish- able from those in WT animals measured at multiple time points postinjection, and this occurred independently of differences in plasma fatty acid levels. Although it has recently been shown that fasting-induced increases in plasma fatty acids are reduced in IL-6-deficient mice (37), this could likely be attributed to reductions in circulating catecholamine levels in these mice (30), as the data from the current study and previous work from our laboratory (32) demonstrate that both in vivo and ex vivo lipolytic responsiveness is intact in IL-6 knockout mice. In addition to normal reductions in blood glucose in response to CL treatment in IL-6-deficient mice, we demonstrate a clear temporal dissociation between increases in plasma IL-6 concentrations and reductions in blood glucose levels following CL treatment.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In support of this, in whole body IL-6 knockout mice, the glucose lowering effects of CL were indistinguish- able from those in WT animals measured at multiple time points postinjection, and this occurred independently of differences in plasma fatty acid levels. Although it has recently been shown that fasting-induced increases in plasma fatty acids are reduced in IL-6-deficient mice (37), this could likely be attributed to reductions in circulating catecholamine levels in these mice (30), as the data from the current study and previous work from our laboratory (32) demonstrate that both in vivo and ex vivo lipolytic responsiveness is intact in IL-6 knockout mice. In addition to normal reductions in blood glucose in response to CL treatment in IL-6-deficient mice, we demonstrate a clear temporal dissociation between increases in plasma IL-6 concentrations and reductions in blood glucose levels following CL treatment.…”
Section: Discussioncontrasting
confidence: 55%
“…Changes in mRNA expression of IL-6 were determined using real-time qPCR as described in detail previously by our laboratory (32,33). RNA was isolated from epididymal white adipose tissue using an RNeasy kit according to the manufacturer's instructions.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…Interestingly, BCAA catabolism can regulate muscular fatty acid β-oxydation via the glyceroneogenesis pathway [67], whose ratelimiting step is the conversion of oxaloacetate to phosphoenolpyruvate by phosphoenolpyruvate carboxykinase. As the expression of the phosphoenolpyruvate carboxykinase gene is strongly inhibited by IL-6 in liver and adipose tissue [68,69], IL-6 blockade could interfere with plasmatic concentrations of glycerol, serine, and branched chain amino acids, as observed in the present study.…”
Section: Moderate Effect On Metabolismsupporting
confidence: 63%
“…Tissue in each dish was minced into 5-10 mg fragments and placed into 4.5 mL M199 supplemented with 1% antibiotic/antimycotic, 50 mU insulin and 2.5 nM dexamethasone. Samples were left to equilibrate for 24 hours at 37 C, at which point the media was removed and changed to M199 supplemented with the same doses of antibiotic and dexamethasone, 2.5% bovine serum albumin (BSA) and no insulin. For the 2-8 hour time course experiment, one dish per depot was treated with each of the following conditions: i) sterile H 2 O (control), ii) 1 mM CL 316,243, iii) 10 nM 17-b-estradiol, or iv) 1 mM CL 316,243 plus 10 nM 17-b-estradiol.…”
Section: Adipose Tissue Organ Culturementioning
confidence: 99%
“…37,38 Insulin and estradiol ELISAs Serum samples from saline-injected SHAM, OVX and OVX E2 rats were analyzed for insulin concentration in duplicate, using a commercially available kit (Millipore EZMRI-13K), as described previously. 39,40 Accuracy and intra-assay comparisons were validated using 2 quality control standards (run in triplicate) provided with each kit.…”
Section: Free Fatty Acid and Glycerol Concentrationsmentioning
confidence: 99%